Civilian students: Victor G. Laties, Robert L. Nichols, Philip A. Bugler, Edward F. M. Wong, Charles L. Beckles, and Charles W. More, 1940 - Munro, Melville S. (Tufts Archival Research Center, 2005)
Print is in Munro Collection, Box 94, p. 56